The role of circumferential strain in the differential diagnosis of cardiomyopathies with left ventricular hypertrabeculation. (8th February 2021) - Szucs, A; Gregor, ZS; Kiss, AR; Horvath, M; Farsang, V; Szabo, LE; Toth, A; Dohy, ZS; Czimbalmos, CS; Merkely, B; Vago, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Supported by the ÚNKP-19-3-II New National Excellence Program of the Ministry for Innovation and Technology Dilated (DCM), hypertrophic (HCM) and noncompaction cardiomyopathy (NCMP) are genetically and morphologically overlapping diseases, however they differ in clinical manifestation, treatment and prognosis. Cardiac MRI feature-tracking might help to differentiate between these cardiomyopathies with left ventricular (LV) hypertrabeculation. We aimed to describe the differences in the functional and strain parameters of NCMP patients with good LV ejection fraction (EF, NCMP-G) compared with patients with HCM, and NCMP patients with reduced EF (NCMP-R) compared with patients with DCM . We included 62 NCMP patients from which 31 had good LV function and 31 had decreased LV-EF. The NCMP-G group was compared with an HCM population (n = 31) and the NCMP-R group was compared with a DCM group (n = 31) matching in age and sex (age, EF; NCMP-G 46.0 ± 13.0 years, 65.5 ± 5.3% vs. HCM 47.2 ± 14.4 years, 74.8 ± 6.3%; NCMP-R 54.5 ± 12.1 years, 32.8 ± 10.1% vs. DCM 50.8 ± 16.7 years, 34.0 ± 8.2%). 1.5 T Philips Achieva and Siemens Aera MRI machines were used for the scans, Medis Suite program was used for analysis and MedCalc software for statistics, p < 0.05 was considered statistically significant. Significant differences were found between the functional parameters of HCM and NCMP-G patients, while the DCM and NCMP-R groups differed only in the trabecular mass values (LV-trab, NCMP-G vs. HCM: 26.2 ± 7.5 vs. 30.7 ± 7.0 g/m2, NCMP-R vs. DCM: 48.2 ± 13.2 vs. 42.1 ± 10.1 g/m2, p < 0.05). The global longitudinal strain values of the studied populations were not significantly different, however the global circumferential strain (GCS) values were significantly better in patients with HCM and DCM compared with the NCMP groups (GCS, NCMP-G vs. HCM: -31.2 ± 4.9 vs. -43.0 ± 8.4%, NCMP-R vs. DCM: -11.7 ± 7.3 vs. -16.9 ± 6.1%). The average circumferential strain values of the LV basal, mid and apical parts were significantly better in the HCM and DCM groups compared with the NCMP groups (NCMP-G vs. HCM: -35.7 ± 9.5 vs. -50.5 ± 14.1%, NCMP-R vs. DCM: -29.5 ± 13.2 vs. -15.6 ± 6, 7%). We assessed the cut-off point of the average LV apical circumferential strain to differentiate the studied populations (HCM vs. NCMP-G cut-off: -47.3% sens.: 83.9%, spec.: 67.7%, AUC: 0.81; DCM vs. NCMP-R cut-off: -19.3% sens.: 83.9%, spec.: 83.9%, AUC: 0.86). The diverse circumferential strain values of the hypertrabeculated LV apical third could help the differential diagnosis of NCMP, DCM and HCM.